Symbolism of the number “four” in English and Kazakh Languages - Kelmaganbetova, A.S.; Omasheva, Zh.M.; Sovetova, Z.S.; Luchik, M. («Академик Е.А. Бөкетов атындағы Қарағанды университеті» КЕАҚ баспасы, 2023)
The article considers the comparative study of the symbolism of English and Kazakh stable combinations, as well as proverbs and sayings with the numerical component “four”. The study revealed both similarities and differences in the symbolism of the number “four” in English and Kazakh languages, which is explained by the universality of the character of the symbols on the one hand and the fact that there is an ethnocultural specificity in the connotative meaning, which is reflected in the culture and language of the people. The universality of the symbolization of numbers is determined by the anthropocentric worldview and the universal system of human development, as well as the desire of a person to explain the structure of the world through the sacred power of numbers. At the end of the article the authors came to conclusion that the numerals with the component four as part of stable combinations in English and Kazakh Languages acquire a symbolic meaning. Stable combinations with the numeral component characterize various aspects of human life: its external qualities and internal properties, behavior, relationships with other people, as well as ideas related to the quantitative and spatial development of the world and the universe.
Ағылшын жəне қазақ тілдеріндегі «төрт» санының символикасы
Символика числа «четыре» в английском и казахском языках
Keywords: number; culture; symbolism; four; phraseological units; stable expressions